Biological Therapy for Inflammatory Bowel Disease - Franco Leal, Raquel; Torriani, Tristan (IntechOpen, 2020)
The treatment of inflammatory bowel disease (IBD) has posed a major challenge since its appearance. Biomedical researchers, physicians, gastroenterologists, and surgeons have struggled to improve the quality of life of their patients and have sought, above all else, to keep the disease under remission for as long as possible. Blockers for tumoral necrosis factor alpha (TNF-α) were the first biological drugs to be discovered and for this reason they played a crucial role in the subsequent evolution of IBD treatment. The aim of this book is to provide an overview of such drugs and the latest developments in IBD immunopathology. Our contributors discuss the main indications, efficacy, and possible side effects of the different types of drugs available today for IBD treatment.